2010
DOI: 10.1039/b926365a
|View full text |Cite
|
Sign up to set email alerts
|

Self-promotion mechanism for CO electrooxidation on gold

Abstract: CO electrooxidation on Au(111), Au(100) and Au(110) electrodes in 0.1 M HClO(4) and 0.1 M NaOH solutions has been studied by means of voltammetric measurements with hanging meniscus rotating bead-type electrodes. It is found that the reaction order in CO concentration is close to unity at potentials close to the onset of CO oxidation, and then it becomes higher than unity at higher potentials for all studied surfaces except for Au(111) in 0.1 M HClO(4). This behavior indicates that CO oxidation on gold takes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 42 publications
9
84
0
Order By: Relevance
“…[49,50] Therefore, the oxidation of methanol and its oxidation reactioni ntermediates on the preferentially oriented nanoparticles is of highi nterest in order to elucidatet he reactionm echanism on these types of catalysts. Previous studies have also shown that the adsorption of one CO monolayer on ag old electrode in alkaline media takes places at lower potentials than 0.3 Vv ersus RHE with further oxidation at potentials highert han 0.7 V. [30][31][32] Additional studies have shown that the CO adsorbed on Au(111)a nd Au(100) promotes the oxidation of methanol and other alcohols. [51] To evaluatet he surface selectivity of CO oxidation on the Au preferentially oriented nanoparticles, as imilar procedure to that used in Ref.…”
Section: Electrochemical Oxidation Of Carbonm Onoxide Methanol and mentioning
confidence: 99%
See 3 more Smart Citations
“…[49,50] Therefore, the oxidation of methanol and its oxidation reactioni ntermediates on the preferentially oriented nanoparticles is of highi nterest in order to elucidatet he reactionm echanism on these types of catalysts. Previous studies have also shown that the adsorption of one CO monolayer on ag old electrode in alkaline media takes places at lower potentials than 0.3 Vv ersus RHE with further oxidation at potentials highert han 0.7 V. [30][31][32] Additional studies have shown that the CO adsorbed on Au(111)a nd Au(100) promotes the oxidation of methanol and other alcohols. [51] To evaluatet he surface selectivity of CO oxidation on the Au preferentially oriented nanoparticles, as imilar procedure to that used in Ref.…”
Section: Electrochemical Oxidation Of Carbonm Onoxide Methanol and mentioning
confidence: 99%
“…[32] The bulk oxidation of carbon monoxide on the nanoparticles did not show surface-structure sensitivity,w hich is in agreement with results described previously in the literature. [22,31,54] Figures 3A and Bs how the voltammetric profiles of methanol and formaldehyde on the cubic and octahedral Au nanoparticles in alkaline medium. For methanol, as can be seen in Figure3A, the voltammetric profiles are quite similar,b oth in terms of the onset of the oxidation( ca.…”
Section: Electrochemical Oxidation Of Carbonm Onoxide Methanol and mentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] However, such approach also present difficulties related to the determination of the charge involved in the electrooxidation. For instance, depending on the metal nature, CO can adsorb on different ways onto a surface, 14,15 which can embed errors in estimating the surface area if pure metals are compared with multi-metallic catalysts. Another regular method is normalizing the current by the mass of the main metal (normally Pt) in multi-metallic catalysts.…”
Section: Introductionmentioning
confidence: 99%